Kemitraan antara Dosen dan Mahasiswa KKN dalam Penyelenggaraan Kegiatan Penyuluhan Pendidikan bagi Masyarakat Desa - novan ardy wiyani (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2022)
This community service activity is aimed at: (1) identifying educational problems in the village where KKN UIN Prof. K.H Saifuddin Zuhri Purwokerto is located in Banyumas district in 2022; and (2) deliver solutions to educational problems through the implementation of educational counseling in the village where the KKN UIN Prof. K.H Saifuddin Zuhri Purwokerto location is located in Banyumas district in 2022. The author uses the Participatory Action Research (PAR) method to carry out community service activities. Service activities are located in Kalisogra village, Kalibagor sub-district, Lumbir village, Lumbir sub-district and several villages in Purwojati sub-district, Banyumas district. The results of community service show that: (1) educational counseling activities are designed and implemented to address social problems in the village; (2) educational counseling activities are carried out in the form of child education counseling for parents, PAUD administrative counseling for PAUD managers and teachers, and religious education counseling for junior high school students.